Electromagnetic Properties of Multifunctional Composites Based on Glass Fiber Prepreg and Ni/Carbon Fiber Veil - Silveira, Daniel Consoli [UNESP]; Gomes, Newton; Rezende, Mirabel Cerqueira; Botelho, Edson Cocchieri [UNESP] (Inst Aeronautica & Espaco-iae, 2017)
Multifunctional composites combine structural and other physicochemical properties, with major applications in aeronautical, space, telecommunication, automotive, and medical areas. This research evaluates electromagnetic properties of multifunctional composites based on glass fiber woven fabric pre-impregnated with epoxy resin laminated together carbon fiber non-woven veil metalized with Ni. In this way, searching for possible application as radar absorbing structures or electromagnetic interference shielding structures. The scattering parameters, in the frequency range of 8.2 to 12.4 GHz, show that the epoxy resin/glass fiber prepreg allows the transmission of the electromagnetic waves through its microstructure, independently of the glass fiber reinforcement orientation (98% transmission, S-24 = -0.09 dB). However, the carbon fiber/Ni veil shows highly reflector behavior (91% reflection, S-22 = -0.43 dB). Energy dispersive spectroscopy of the veil, before and after nitric acid attacks, confirmed the Ni coating removal from the carbon fiber surface. Still, the scattering parameters show reflector behavior (77% reflection, S-22 = -1.13 dB), attributed to the electrical conductivity of carbon fibers. Multifunctional composites based on glass fiber/epoxy/carbon fiber/Ni veil laminates were processed by hot compression molding. The scattering parameters show that the laminates do not behave as good radar absorbing structures. Nevertheless, the laminates present promising results for application as light weight and low thickness structural composites with electromagnetic interference shielding effectiveness (91.4% reflection for 0.36 mm thickness and 100% for similar to 1.1 mm) for buildings, aircraft, and space components.
Keywords: Composite structures; Microwave absorption; Electromagnetic shielding; Glass fiber reinforced plastics; Carbon fiber reinforced plastics